Pro- and anti-inflammatory Cytokines in Coronavirus Disease 2019 (Medico Legal Update, 2020)
It has long been believed that cytokines have an important function in immunopathology during viralinfection. Coronavirus disease 2019 (Covid-19) is a contagious viral disease caused by severe acuterespiratory syndrome coronavirus 2. Covid-19 can be fatal because of an overactive immune response andrelease of cytokines. This review focuses on the role of cytokines in COVID-19.